DEVELOPMENT OF QUARTET CARD LEARNING MEDIA ON THE MATERIAL OF GREAT WORLD CIVILIZATIONS: Pengembangan Media Pembelajaran Kartu Kuartet pada Materi Peradaban Besar Dunia - Muhammad Sandiawan Fatulloh; Romadi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to develop a quartet card learning media for the topic of Great World Civilizations and to evaluate its feasibility based on expert validation. The research employs a Research and Development (R&D) approach using the 4D model, which includes the stages of define, design, and develop, while the dissemination stage is not conducted due to the study’s focus on product feasibility. Data were collected through validation sheets completed by subject matter experts and media experts, and analyzed using descriptive quantitative techniques. The results indicate that the developed learning media meets high feasibility standards. Media validation results improved from 68.3% (feasible with revision) to 91.6% (highly feasible), while material validation increased from 82.1% (very valid with minor revision) to 91% (highly valid). These findings demonstrate that the quartet card media is both valid and appropriate for use in history learning. The media integrates visual elements, concise textual information, and QR codes to support interactive and independent learning. This study contributes to the development of game-based learning media in history education, particularly for complex and abstract materials such as world civilizations. Practically, the developed media offers an innovative, engaging, and accessible alternative to enhance students’ understanding and participation. Further research is recommended to examine its effectiveness in classroom implementation.